What are the chances? : voodoo deaths, office gossip, and other adventures in probability - Holland, Bart K. (Johns Hopkins University Press, 2002)
"Our lives are governed by chance. But what, exactly, is chance? In this book, accomplished statistician and storyteller Bart K. Holland takes us on a tour of the world of probability. Weaving together tales from real life - from the spread of the bubonic plague in medieval Europe or the number of Prussian cavalrymen kicked to death by their horses, through IQ test results and deaths by voodoo curse, to why you have to wait in line for rides at Disneyworld - Holland captures the reader's imagination with surprising examples of probability in action, everyday events that can profoundly affect our lives but are controlled by just one number."--Jacket